Impact of OCTAPACE Model on Banking Employees: a Comparative Study of Private and Public Sector Banks with reference to Andhrapradesh (International Journal of Innovative Research in Engineering & Management, 2022)
Organisational culture is a facet that impacts every organisation’s functioning, different  organisation needs different quite culture to be set up. it’s  defined in terms of shared meaning, patterns of beliefs,  rituals, symbols, and myths that evolve over time, service to  scale back human variability and control and shape  employee behavior in organisation. this research aims to  compare private sector and public sector banks in terms of  values of employees. The study attempts to understand the  impact of OCTAPACE model on banking employees of  private and public sector banks in Andrapradesh.The main  implication of this research on organisational culture  suggest that there is a scope for further improvement in the  sample study organisations which would improve their work  life by overcoming the monotony.
Keywords: OCTAPACE; Organisational Culture; Bank